Cross-cultural Counselling: Some Special Problems and Possible Directions for the Canadian Counsellor - Westwood, Marvin J. (Canadian Journal of Counselling and Psychotherapy, 2012)
The need for developing particular skills for working with clients who are racially or culturally dissimilar from the counsellor is becoming increasingly apparent; especially in the Canadian society. Problems for both client and counsellor do occu rin the cross-cultural situation. The more frequent difficulties are discussed and recommendations for ways in which counsellors and counsellor educators can meetthis challenge are discussed.